Pengembangan Media Video Animasi Pembelajaran Berbasis Pendekatan Inkuiri pada Mata Pelajaran Bahasa Inggris Kelas VIII SMP - Yuninda Rekka, Yuninda Rekka Puttri; Hendri, Nofri; Darmansyah, Darmansyah; Yusri, Meldi Ade Kurnia (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The development of learning video media is carried out as an effort to solve student learning problems. This Learning Media can be used as an alternative to reduce problems in learning. This study aims to produce products in English class VIII subjects and determine the quality of validity and practicality of the products developed so that they are feasible to use. This study is a type of Research and Development (R&D) development or by using a 4-D development model (four-D model). This Model consists of 4 stages of development include Define, Design, Develop, Disseminate. The product validity test was conducted by 3 validators, namely 2 media validators and 1 material validator. Practicalities test was conducted on 31 students of Class VIII SMP Negeri 1 Junjung Sirih. The results of this study explain that the average percentage of media validators I and II respectively is 97.5% and 96.25% with the category of